Development of an Integrated Discovery Learning E-Book on Tabuik to Improve Students' Critical Thinking Abilities and Collaborative Attitudes - Rahmat Syaifullah; Zuhdan Kun Prasetyo (STAI Hubbulwathan Duri, 2025)
This study aims to evaluate the validity, readability, practicality, and effectiveness of an Integrated Discovery Learning E-Book based on the Tabuik cultural tradition to enhance students’ critical thinking skills and collaborative attitudes. The research followed the 4D development model (Define, Design, Develop, Disseminate) and was implemented at SMP Negeri 25 Padang. The validity of the e-book was assessed by three expert lecturers. Readability and practicality were evaluated by 31 students and 3 teachers. To test effectiveness, 93 students participated. Data from the validity, readability, and practicality tests were analyzed using standard rating scales. Effectiveness data were analyzed using the General Linear Model (GLM), specifically MANOVA. The e-book received a validity score of 76 (very high), a readability score of 63.35 (good), and a practicality score of 19.33 (very good). The GLM test showed a significance value 0.05, indicating a statistically significant improvement. Students’ critical thinking and collaborative attitudes improved, with N-gain scores of 0.73 and 0.71, respectively—both categorized as high. The findings confirm that the developed e-book is not only educationally sound but also culturally relevant and engaging, promoting higher-order thinking and social skills among students. The Tabuik-based e-book is valid, readable, practical, and effective in enhancing critical thinking and collaboration. Future studies should explore incorporating a broader range of cultural elements for more generalized outcomes.